Pharmacoepidemiology of Antiretroviral Drugs in a Tertiary Care Teaching Hospital - Pragna Malavika Malavika B; Saravana Kumar RT; Lakshmi BVS (Journal of Global Pharma Technology, 2020)
Background: India has a large population using antiretroviral drugs (ARV) which has potential therapeutic efficacy and high toxic properties resulting in diverse adverse drug reactions (ADRs). Adherence to the ART is a crucial challenge to be addressed as it plays a major role in the success of HIV management. Aim: To determine the prescribing pattern of antiretroviral drugs uses at an ART center and the levels of adherence to the drugs and the associated adverse effects. Materials and methods: It is a retrospective analysis of the clinical records related to HIV-infected adults who were receiving treatment at an ART Center in Andhra Pradesh state. The main outcomes of the study are demographic details of the patients, the pattern of ART combinations prescribed, adherence to the given ART, and analysis of reported ADRs. Simple descriptive statistics and chi-square tests are the statistics used to measure the outcomes. Results: A total of 430 HIV patients’ records were selected and assessed. Tenofovir (TAF)+ Lamivudine (3TC) +Efavirenz (EFV) (66.5%) was the most prescribed ARV combination. The majority of 348 patients (80.9%) were good adherence and showed a significant association with therapeutic outcomes. The most common clinical ADRs found in this study were gastrointestinal disturbances (30.9%) followed by dermatological problems (20.4 %). Conclusion: Despite drug toxicity, ART treatment bears potential therapeutic efficacy and is considered as the only means to increase life expectancy in HIV infected patients. Detailed patient counseling and monitoring improve therapeutic outcomes and patients adherence.